THE POLICY OF HISTORICAL MEMORY IN POLAND-GERMANY RELATIONS: METHODOLOGICAL APPROACH - Бойчук, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Politics of history means the use of the past and narrations of the past for achieving political preferences. Of course, politics of history can be used for creations the identity of nation or society, also. Currently, the using history in political and social life is strongly high. Especially, the using history has observed in Poland. The purpose of this research – on case study Poland and Germany – to show the thoughts and views of Poland` and Germany` researchers towards understanding this process. Policy of past, mainly, is dedicated to looking on the process in this field and, also is discovered the role of society, it initiative. Policy of history is discovered the role of state in this process. Mostly, researches have a negative attitude towards state` intervention in this field. But, almost everyone are pointing out this intervention are playing crucial role for creation common identity among society. Policy of past, mostly is characteristic for Germany, as opposed to policy of history, which have a place in Central East Countries. The work shows two main approaches, which are different by initiators – state led and social driven. Also, the article is dedicated to analyzing why in the last time is so strongly interest among society and politicians, particularly in Poland.